A moderated mediation examination of shared leadership and team creativity: a social information processing perspective - Ali, Ahsan; Wang, Hongwei; Boekhorst, Janet A. (Asia Pacific journal of management, 2023)
Research has mostly focused on how formal leadership can shape a climate for innovation, but we know little about how informal leadership, such as shared leadership, may affect this process. Departing from this dominant focus, we examine how shared leadership may have a positive influence on team processes and performance. Based on social information processing theory, we develop a moderated mediation model that examines the indirect effect of shared leadership on team creativity via a climate for innovation and further investigates the moderating effect of task uncertainty. Two survey-based field studies using multisource, multiwave data support the hypothesized model. The findings reveal that (1) shared leadership positively predicts a climate for innovation, (2) this relationship is stronger when the team faces task uncertainty, (3) a climate for innovation positively predicts team creativity, (4) shared leadership predicts team creativity through the mediating effect of a climate for innovation, and (5) this mediation effect is stronger when task uncertainty is high. Theoretical and practical implications are discussed.